Credit Ratings and CEO Risk‐Taking Incentives - Kuang, Yu Flora; Qin, Bo (Contemporary Accounting Research, 2013)
This study examines the sophistication of rating agencies in incorporating managerial risk‐taking incentives into their credit risk evaluation. We measure risk‐taking incentives using two proxies: the sensitivity of managerial wealth to stock return volatility ( vega ) and the sensitivity of managerial wealth to stock price ( delta ). We find that rating agencies impound managerial risk‐taking incentives in their credit risk assessments. Assuming other things equal, a one standard deviation increase in vega ( delta ) will lead to an approximately one‐notch (two‐notch) rating downgrade. In addition, we evaluate the significance of credit ratings in the design of CEO compensation. Our findings suggest that rating‐troubled firms will gear down managerial incentives of risk seeking. In particular, other things equal, a rating downgrade to the lower edge of the investment category (i.e., BBB−) in the immediate prior year will bring about an approximately 51 percent reduction of vega incentive from options newly granted to the CEO in the current year. However, we find no evidence that firms' rating concerns significantly affect delta . Given the significance of credit ratings in the marketplace and their close connection to accounting, the findings of the current study advance our understanding, not only of how sophisticated rating agencies are in incorporating forward‐looking information (i.e., vega and delta ) into risk assessments, but of how influential the raters are in changing firms' compensation policies. The findings also have implications on the role of accounting in constraining excessive managerial risk taking with improved disclosures on managerial compensation.